Social Entrepreneurship Orientation and Enterprise Fortune: An Intermediary Role of Social Performance - Zafar, Zuhaib; Wenyuan, Li; Bait Ali Sulaiman, Mohammed Ali; Siddiqui, Kamran Akhtar; Qalati, Sikandar Ali (Frontiers in Psychology, 2022)
Social entrepreneurship orientation (SEO) is a behavioral construct of social entrepreneurship; therefore, it was examined that the influence of social entrepreneurship orientation (SEO) of the organization on social and financial performance. A random sample of 810 employees was drawn from social enterprises of Pakistan during Covid-19 time. Although increasing research concerns in social entrepreneurship, the discipline continues to disintegrate, and this has extended to appeals a careful investigation of the associations of firms' social entrepreneurship. In the recent decade, "social entrepreneurship" has earned its importance as a segment of entrepreneurship. Instead of mixed activity, firms are more likely to engage in either for-profit or non-profit activities. The causes for and consequences of this conduct has been mainly studied using objective measures of social entrepreneurship orientation, social performance, and financial performance, with little attention paid to the subjective experiences of social enterprises. We rely on the theory of stakeholder and mixed structuring to postulate that social performance intermediates the SEO-financial performance relation. By assessing a sample of 810 from active enterprises, we discover that social performance mediates positively and partially between SEO and financial performance, and both direct and indirect paths were in the same direction and significant. Our findings exhibit that social performance variance explained 74% of mediating role, and the remaining 26% effect is because of SEO. We consider the functions by which an SEO influences enterprise performance and delivers more prominent understandings into multiple spectrums of performance. We discourse the prospective suggestions of our research and foster an encouraging pathway for more enquiry on the SEO paradigm. The study adds contribution to the literature, and that has not been testified before on hybrid firms. Despite SEO being a newly defined construct and it requires more prospective research. This research gives the researchers/scholars new directions to address related disciplines and further explore this domain.